2022
DOI: 10.1126/sciadv.abm0478
|View full text |Cite
|
Sign up to set email alerts
|

eIF4A2 targets developmental potency and histone H3.3 transcripts for translational control of stem cell pluripotency

Abstract: Translational control has emerged as a fundamental regulatory layer of proteome complexity that governs cellular identity and functions. As initiation is the rate-limiting step of translation, we carried out an RNA interference screen for key translation initiation factors required to maintain embryonic stem cell (ESC) identity. We identified eukaryotic translation initiation factor 4A2 (eIF4A2) and defined its mechanistic action through ribosomal protein S26–independent and –dependent ribosomes in translation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 78 publications
2
17
0
Order By: Relevance
“…We validated these five candidates by repeating the shRNA experiment in another mouse ESC line, CCE, with the same protocol described (Figure 1A ), and confirmed that the pluripotency loss and the differentiation induction were reproducible and consistent with the target KD efficiency ( Supplementary Figure S2A, B ). Among these five candidates, Ddx2b ( 28 , 29 ), Ddx6 ( 30–33 ), Ddx18 ( 34 ) and Ddx47 ( 35 ) were previously reported to play important roles in ESCs, not only validating our screening results but also highlighting Ddx48 as a novel candidate. Examination of their expression levels among various tissues and cell lines revealed that, like Ddx18, Ddx48 is also particularly enriched in ESCs ( Supplementary Figure S3 ), indicating its ESC-specific roles.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…We validated these five candidates by repeating the shRNA experiment in another mouse ESC line, CCE, with the same protocol described (Figure 1A ), and confirmed that the pluripotency loss and the differentiation induction were reproducible and consistent with the target KD efficiency ( Supplementary Figure S2A, B ). Among these five candidates, Ddx2b ( 28 , 29 ), Ddx6 ( 30–33 ), Ddx18 ( 34 ) and Ddx47 ( 35 ) were previously reported to play important roles in ESCs, not only validating our screening results but also highlighting Ddx48 as a novel candidate. Examination of their expression levels among various tissues and cell lines revealed that, like Ddx18, Ddx48 is also particularly enriched in ESCs ( Supplementary Figure S3 ), indicating its ESC-specific roles.…”
Section: Resultssupporting
confidence: 85%
“…We also noticed that, upon eIF4A3 KD, the reduction of Cyclin B1 protein was more pronounced than that of eIF4A3 (Figure 6G , H ) and that the RPF reduction on Ccnb1 mRNA mainly happens at the translation initiation region (5′ UTR and the beginning of the coding region) (Figure 5D , shaded in purple, the RPF tracks). In ribosome profiling, it is well known that for the proteins bound at translation initiation regions, their expression changes can lead to RPF alteration mainly at these translation initiation regions, with much less or even no alteration on the rest of mRNA bodies, and such a reduction can dramatically decrease the protein levels of these mRNAs ( 29 ). This could apply to eIF4A3 KD-induced Ccnb1 change in our study, considering that eIF4A3 is mainly bound around the first exon–exon junction of Ccnb1 mRNA with the enrichment at the translation initiation region (Figure 5D ).…”
Section: Discussionmentioning
confidence: 99%
“…We further detected 16 ZNF genes that exhibit a co-expression pattern with the histone genes in the specific stem cell and growth conditions (Figure 6B and C ), of which seven genes were closely located within chromosome 19 (13q42-13q43) (Figure 6D ). Previous studies reported the connection between stem cell identity and histones or zinc fingers: the activation of multiple histone variants, including H1, H2A and H3, in maintaining ESC pluripotency and ESC fate ( 103 , 104 ), the role of histone variant H3.3 on the maintenance of HSC stemness ( 105 ), and co-localized 31 zinc-finger genes within topologically associating domains on chr19 in human ESCs ( 106 ). We found a higher co-expression pattern between histones and co-localized zinc fingers in ESCs in xenogenic medium and HSCs in L-GLN medium (Figure 6A and C ).…”
Section: Discussionmentioning
confidence: 99%
“…Tubulin alpha chain and beta chains, Vimentin as well as Eif4a2 and Pdia6 (Supplementary Data 8 ). These two factors are known to be involved in stem cell pluripotency [ 48 ] and metastasis [ 49 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%